Cardiovascular disease in Adult Life after Childhood Cancer in Scandinavia: A population‐based cohort study of 32, 308 one‐year survivors. Issue 5 (14th March 2015) - Gudmundsdottir, Thorgerdur; F. Winther, Jeanette; de Fine Licht, Sofie; G. Bonnesen, Trine; H. Asdahl, Peter; Tryggvadottir, Laufey; Anderson, Harald; Wesenberg, Finn; Malila, Nea; Hasle, Henrik; H. Olsen, Jørgen; on behalf of the ALiCCS study group
<x xml:space="preserve">Abstract</x> The lifetime risk for cardiovascular disease in a large cohort of childhood cancer survivors has not been fully assessed. In a retrospective population‐based cohort study predicated on comprehensive national health registers, we identified a cohort of 32, 308 one‐year survivors of cancer diagnosed before the age of 20 in the five Nordic countries between the start of cancer registration in the 1940s and 1950s to 2008; 211, 489 population comparison subjects were selected from national population registers. Study subjects were linked to national hospital registers, and the observed numbers of first hospital admission for cardiovascular disease among survivors were compared with the expected numbers derived from the population comparison cohort. Cardiovascular disease was diagnosed in 2, 632 childhood cancer survivors (8.1%), yielding a standardized hospitalization rate ratio (RR) of 2.1 (95% CI 2.0–2.2) and an overall absolute excess risk (AER) of 324 per 100, 000 person‐years. At the end of follow‐up 12% of the survivors were ≥ 50 years of age and 4.5% ≥ 60 years of age. Risk estimates were significantly increased throughout life, with an AER of ∼500–600 per 100, 000 person‐years at age ≥ 40. The highest relative risks were seen for heart failure (RR, 5.2; 95% CI 4.5–5.9), valvular dysfunction (4.6; 3.8–5.5) and cerebrovascular diseases (3.7; 3.4–4.1). Survivors of hepatic tumor, Hodgkin lymphoma and leukemia had the highest overall risks for cardiovascular disease, although each main type of childhood cancer had increased risk with different risk profiles. Nordic childhood cancer survivors are at markedly increased risk for cardiovascular disorders throughout life. These findings indicate the need for preventive interventions and continuous follow‐up for this rapidly growing population.